Structural Elucidation and Antioxidant Activities of a Neutral Polysaccharide From Arecanut (Areca catechu L.) - Ji, Xiaolong; Guo, Jianhang; Pan, Feibing; Kuang, Fengjun; Chen, Haiming; Guo, Xudan; Liu, Yanqi (Frontiers in Nutrition, 2022)
A novel neutral polysaccharide designated as PAP1b was isolated from Areca catechu L. by hot water extraction, ethanol precipitation and column chromatography. PAP1b was mainly composed of mannose, galactose, xylose and arabinose in a ratio of 4.1:3.3:0.9:1.7, with an average molecular weight of 37.3 kDa. Structural characterization indicated that the backbone of PAP1b appeared to be composed mainly of →6)-β-D-Manp-(1→, →4)-α-D-Galp-(1→ and →3,6)-β-D-Manp-(1→ residues with some branches, and terminal of (1→)-linked-β-D-Manp residues. The results of bioactivity experiments showed that PAP1b had antioxidant in vitro, especially on scavenging DPPH and hydroxyl radicals. Therefore, the polysaccharide from Areca catechu L. could be used as a potential antioxidant in functional food.